ANALISIS PENGARUH VIRAL MARKETING TERHADAP PURCHASE INTENTION DENGAN BRAND IMAGE DAN BRAND AWARENESS SEBAGAI VARIABEL INTERVENING PRODUK MS GLOW (STUDI PADA PENGGUNA TWITTER INDONESIA) - Shanerika Salina; Budi Sudaryanto (Diponegoro Journal of Management, 2023)
ABSTRACT Local brand competition, especially in the skincare category, continues to increase, one of the popular local products is MS Glow. Evidence of MS Glow's difficulty in competing in skincare sales is the emergence of issues that have an impact on decreasing public interest and interaction with related brands coupled with data showing that the volume of purchases has decreased, so that MS Glow needs to carry out various strategies to survive. The influence of the use of viral marketing has resulted in the rapid spread of viral issues regarding the local self-care brand MS Glow through social media Twitter and elicited responses and views from various Indonesian Twitter users towards MS Glow, so that factors such as viral marketing, brand image, and brand awareness can be a solution offered by researchers in increasing interest in purchasing MS Glow which is supported by pre-survey data. Using a nonprobability-sampling approach, data were obtained from Indonesian Twitter users through a quantitative questionnaire in the form of a Google form containing closed questions with an interval scale of 1-10. Analysis was carried out using the Structural Equation Model (SEM) method using AMOS software. The results of the study state that viral marketing has a negative effect on brand image and brand awareness but has a positive and significant effect on purchase intention, brand image has a positive and significant effect on purchase intention, and brand awareness has a negative effect on purchase intention. The use of viral marketing requires the right methods and handling to be successful and have a positive and significant effect.